Editorial (English) - Mota, Maurício (REVISTA QUAESTIO IURIS, 2016)
Editorial for vol. 09-3 (2016) The Journal Quaestio Iuris, journal classified by MEC / CAPES as Qualis A2, Law, now quarterly, in this volume 09, number 03, is pleased to publish the article Essay about the inter-relationship of philosophy, law and deep ecology of Professor Vicente de Paulo Barretto, Dean of the School of Law of the University of Vale do Rio dos Sinos - UNISINOS, visiting Professor of Law Faculty of the University of Coimbra, Consultant ad hoc of law and Philosophy at CAPES of and Editorial adviser of Journal Quaestio Iuris and Fabio Beltrami, PhD in Public Law at the University of Vale do Rio dos Sinos - UNISINOS and professor at Cenecista Higher Education Center Ragamuffin - Ragamuffin CNEC and Faculty of Serra Gaucha - FSG. This Essay about the inter-relationship of philosophy, law and deep ecology analyzes the relationship between man and nature, which has always been subject of inquiry in various branches, from religion to science. The article seeks to elucidate the questions of how to relate these two poles from the human behavioral relation to the areas of law, from three perspectives of thought: anthropocentrism, ecology and several liabilities.